Les débuts de la fonte ornementale en France, de l’Empire à la monarchie de Juillet - Jean‑Paul Zitt (Les Cahiers de l'École du Louvre)
The article touches on the early days of ornamental cast iron in France, from the Empire to the July Monarchy. Examining the actors and their models, it attempts to apprehend the dynamics of the new technique, from its difficult development to its boom years, by looking at it in the perspective of the rapid social changes taking place. The singularity of the material, which combines strength, malleability and low cost, made it emblematic of the “mass‑ produced ornaments” proliferating in cities. Ornamental cast iron provoked strong criticism. Its legitimacy and “sincerity” were called into question in relation to wrought iron, bronze and stone, heralding the “art and industry” debates that would develop as the century progressed. And yet it made an essential contribution to the modernization of the city, and to the improvement and embellishment of the everyday lives of its inhabitants.